Chemokine-Dependent Neutrophil Recruitment in a Murine Model of Legionella Pneumonia: Potential Role of Neutrophils as Immunoregulatory Cells - Tateda, Kazuhiro (American Society for Microbiology, 2001)
The roles of CXC chemokine-mediated host responses were examined with an A/J mouse model of Legionella pneumophila pneumonia. After intratracheal inoculation of 10(6) CFU of L. pneumophila, the bacterial numbers in the lungs increased 10-fold by day 2; this increase was accompanied by the massive accumulation of neutrophils. Reverse transcription-PCR data demonstrated the up-regulation of CXC chemokines, such as keratinocyte-derived chemokine, macrophage inflammatory protein 2 (MIP-2), and lipopolysaccharide-induced CXC chemokine (LIX). Consistent with these data, increased levels of KC, MIP-2, and LIX proteins were observed in the lungs and peaked at days 1, 2, and 2, respectively. Although the administration of anti-KC or anti–MIP-2 antibody resulted in an approximately 20% decrease in neutrophil recruitment on day 2, no increase in mortality was observed. In contrast, the blockade of CXC chemokine receptor 2 (CXCR2), a receptor for CXC chemokines, including KC and MIP-2, strikingly enhanced mortality; this effect coincided with a 67% decrease in neutrophil recruitment. Interestingly, anti-CXCR2 antibody did not affect bacterial burden by day 2, even in the presence of a lethal challenge of bacteria. Moreover, a significant decrease in interleukin-12 (IL-12) levels, in contrast to the increases in KC, MIP-2, and LIX levels, was demonstrated for CXCR2-blocked mice. These data indicated that CXCR2-mediated neutrophil accumulation may play a crucial role in host defense against L. pneumophila pneumonia in mice. The increase in lethality without a change in early bacterial clearance suggested that neutrophils may exert their protective effect not through direct killing but through more immunomodulatory actions in L. pneumophila pneumonia. We speculate that a decrease in the levels of the protective cytokine IL-12 may explain, at least in part, the high mortality in the setting of reduced neutrophil recruitment.